A Rare Case of Recurrence of Craniopharyngioma at Ectopic Site after Surgical Resection of Primary Tumor - Dey, Subir; Rao, Akhilesh; Sinha, Shilpa; Nishant; Kumar, Sanjay (Indian Journal of Neurosurgery, 2018)
Ectopic recurrence of craniopharyngiomas after surgical resection of primary lesion is extremely rare. In this article, the authors describe a case of a 12-year-old girl with ectopic recurrence of craniopharyngioma in an extra-axial location in the right frontal region, after an attempt to completely resect the lesion originally located in the sellar region. The patient was investigated radiologically, hormonally, and histopathologic confirmation was sought. During surgery, it is important to take extra care in removing the primary lesion in toto. In case of cystic tumors, it is very important to aspirate cystic fluid completely, before resecting the capsule to avoid rupture or spillage. Long-term clinical and radiologic follow-up is suggested as ectopic recurrence may occur at a very late stage.
Keywords: craniopharyngioma; ectopic; recurrence